2010
DOI: 10.1038/nature09054
|View full text |Cite
|
Sign up to set email alerts
|

GaAs photovoltaics and optoelectronics using releasable multilayer epitaxial assemblies

Abstract: Compound semiconductors like gallium arsenide (GaAs) provide advantages over silicon for many applications, owing to their direct bandgaps and high electron mobilities. Examples range from efficient photovoltaic devices to radio-frequency electronics and most forms of optoelectronics. However, growing large, high quality wafers of these materials, and intimately integrating them on silicon or amorphous substrates (such as glass or plastic) is expensive, which restricts their use. Here we describe materials and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
489
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 546 publications
(503 citation statements)
references
References 29 publications
3
489
0
Order By: Relevance
“…Disadvantages, compared with non-concentrating PV, arise from complexity associated with the optics and trackers, challenges in module assembly, difficulties in thermal management and inefficiencies in the capture of diffuse light. Recently developed microscale compound semiconductor multijunction cells, miniaturized optics and advanced manufacturing approaches address many of these issues 6 . Even these systems do not, however, function effectively in geographic locations where levels of direct normal irradiance are low, or in applications that demand mechanically flexible modules.…”
mentioning
confidence: 99%
“…Disadvantages, compared with non-concentrating PV, arise from complexity associated with the optics and trackers, challenges in module assembly, difficulties in thermal management and inefficiencies in the capture of diffuse light. Recently developed microscale compound semiconductor multijunction cells, miniaturized optics and advanced manufacturing approaches address many of these issues 6 . Even these systems do not, however, function effectively in geographic locations where levels of direct normal irradiance are low, or in applications that demand mechanically flexible modules.…”
mentioning
confidence: 99%
“…4,5 For device applications, the growth of amorphous inorganic semiconductors 6,7 and organic thin films 8 on amorphous substrates has widely been studied. However, the devices based on single-crystalline compound semiconductors such as GaN show much higher efficiencies, reliability and long-term stability.…”
Section: Introductionmentioning
confidence: 99%
“…This device demonstrated that the attainment of high efficiencies at 1000 suns and above is a reachable and realistic target. However, despite this excellent result it is clear that a dualjunction solar cell −though having interesting applications in approaches that aim substrate reuse, need substrate removal [4] or spectral splitting− has a limited efficiency potential when compared to state-of-the-art triple-junction solar cells. Accordingly, this methodology for UHCPV design is being applied to the development of lattice matched GaInP/GaInAs/Ge triple-junction devices, with the goal of achieving efficiencies in excess of 40% at 1000 suns and above.…”
Section: A From Dual-junction To Triple Junctionmentioning
confidence: 98%